2018
DOI: 10.1080/21645515.2018.1514228
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster vaccination in systemic lupus erythematosus: the current status

Abstract: Among the inflammatory rheumatic diseases, SLE is associated with the highest risk of herpes zoster reactivation relative to age. The reported incidence of herpes zoster infection in SLE ranges from 6.4 to 91.4/1000 patient-years, with main risk factors being major organ disease, immunosuppressive and biological therapies. Although herpes zoster in SLE is manageable with anti-viral treatment, complications such as superimposed bacterial infection, post-herpetic neuralgia may ensue. The low rate of herpes zoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Despite the increased risk of HZ infection, SLE had the lowest HZ vaccination rates among age-eligible subjects,9 probably because of the concern of vaccine safety, the principle of contraindication to live-attenuated vaccines in immunocompromised hosts, as well as the current ambiguous guidelines for HZ vaccination in SLE 10. The US Centers for Disease Control and Prevention only recommends the live-attenuated HZ vaccine in patients receiving low-to-moderate immunosuppression such as short-term corticosteroid therapy (<14 days), low to moderate doses of corticosteroid (<20 mg/day prednisolone), methotrexate (<0.4 mg/kg/week) and azathioprine (<3 mg/kg/day) 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the increased risk of HZ infection, SLE had the lowest HZ vaccination rates among age-eligible subjects,9 probably because of the concern of vaccine safety, the principle of contraindication to live-attenuated vaccines in immunocompromised hosts, as well as the current ambiguous guidelines for HZ vaccination in SLE 10. The US Centers for Disease Control and Prevention only recommends the live-attenuated HZ vaccine in patients receiving low-to-moderate immunosuppression such as short-term corticosteroid therapy (<14 days), low to moderate doses of corticosteroid (<20 mg/day prednisolone), methotrexate (<0.4 mg/kg/week) and azathioprine (<3 mg/kg/day) 22.…”
Section: Discussionmentioning
confidence: 99%
“…However, the definition of ‘less serious’ immunosuppression is not explicit. The recent availability of the non-live subunit and inactivated HZ vaccines might provide more opportunities for SLE patients to be protected against HZ reactivation as they do not contain the live virus that may cause disseminated infection in patients on heavy immunosuppression 10. Despite the lack of head-to-head comparative studies, a recent network meta-analysis showed that the recombinant adjuvant subunit vaccine may be more effective than the live vaccine in preventing HZ reactivation in older healthy individuals 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12 However, these factors are inconsistent across studies, probably because of small samples, selection bias and the heterogeneity of patients included. 19 Moreover, specific rates of herpes zoster reactivation in well-defined subsets of SLE patients have not been reported before. In view of the paucity of data in Chinese patients, this work was conducted to look at the incidence of herpes zoster infection in patients with biopsy proven lupus nephritis undergoing immunosuppressive therapies.…”
Section: Introductionmentioning
confidence: 97%
“…Patients with active SLE who need more intensive immunosuppressive (IS) therapy were more predisposed to VZV infections 5 6. However, mild or even inactive patients could also have VZV infections, and they account for about two-thirds of the events 5–7. A case–control study has described that there was close association between VZV reactivation and SLE diagnosis 8.…”
Section: Introductionmentioning
confidence: 99%